2017
DOI: 10.1002/cbf.3255
|View full text |Cite
|
Sign up to set email alerts
|

Differential activities of peroxisomes along the mouse intestinal epithelium

Abstract: The presence of peroxisomes in mammalian intestine has been revealed formerly by catalase staining combined with electron microscopy. Despite the central role of intestine in lipid uptake and the established importance of peroxisomes in different lipid-related pathways, few data are available on the physiological role of peroxisomes in intestinal metabolism, more specifically, α-, β-oxidation, and etherlipid synthesis. Hence, the peroxisomal compartment was analyzed in more detail in mouse intestine. On the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 68 publications
(109 reference statements)
0
14
0
Order By: Relevance
“…For example, peroxisomes are increasingly recognized as mediators of neural trophic survival and function in the brain, in the production of specialized lipid species like plasmalogens, and for muscle function (Braverman et al ., 2013). The notable abundance of peroxisomes in gut epithelial cells (Novikoff and Novikoff, 1972; Beard and Holtzman, 1987; Faust et al ., 2014; Morvay et al ., 2017) prompted us to investigate a potential role for peroxisomes in the maintenance and regulation of gut epithelial physiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, peroxisomes are increasingly recognized as mediators of neural trophic survival and function in the brain, in the production of specialized lipid species like plasmalogens, and for muscle function (Braverman et al ., 2013). The notable abundance of peroxisomes in gut epithelial cells (Novikoff and Novikoff, 1972; Beard and Holtzman, 1987; Faust et al ., 2014; Morvay et al ., 2017) prompted us to investigate a potential role for peroxisomes in the maintenance and regulation of gut epithelial physiology.…”
Section: Discussionmentioning
confidence: 99%
“…, 2013). Because peroxisomes are notably abundant in gut epithelial cells (Novikoff and Novikoff, 1972; Beard and Holtzman, 1987; Faust et al ., 2014; Morvay et al ., 2017) and because gastrointestinal bleeding has been reported in PBD patients (Lodhi and Semenkovich, 2014), we investigated a potential requirement for peroxisomes in maintaining the structure and function of the gut epithelium using Drosophila as a model. Studies of the Drosophila gut have been at the forefront of recent research on host–commensal and host–pathogen interactions, innate immune signaling, and the regenerative capacity of the intestinal epithelia (Buchon et al.…”
Section: Introductionmentioning
confidence: 99%
“…They degrade prostaglandins, amino acids, polyamines, and purines, and are commonly enriched in the kidneys, liver, pancreas and adrenal glands, which are involved in fat metabolism and detoxification (Magalhães and Magalhães, 1997;Bradford, 2007;Ferdinandusse et al, 2009;Hasegawa et al, 2010;Smith and Aitchison, 2013;Vasko, 2016;Baboota et al, 2019). Furthermore, they are implicated in lipogenic and ROS signaling roles in the heart and intestines (Colasante et al, 2015;Morvay et al, 2017). In the central nervous system (CNS) in particular, peroxisomes synthesize lipids that make up the myelin sheath and cellular membranes, as well as ether phospholipids in neurons and glia; peroxisome dysfunction is also known to impair neuronal migration and membranes (Farooqui and Horrocks, 2001;Powers, 2001;Bottelbergs et al, 2010;Kassmann, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They degrade prostaglandins, amino acids, polyamines, and purines, and are commonly enriched in the kidneys, liver, pancreas and adrenal glands, which are involved in fat metabolism and detoxification (Magalhães and Magalhães 1997, Bradford 2007, Ferdinandusse, Denis et al 2009, Hasegawa, Wakino et al 2010, Vasko 2016, Baboota, Shinde et al 2019. Furthermore, they are implicated in lipogenic and ROS signaling roles in the heart and intestines (Colasante, Chen et al 2015, Morvay, Baes et al 2017). In the central nervous system (CNS) in particular, peroxisomes synthesize lipids that make up the myelin sheath and cellular membranes, as well as ether phospholipids in neurons and glia; peroxisome dysfunction is also known to impair neuronal migration and membranes (Farooqui and 2 Horrocks 2001, Powers 2001, Bottelbergs, Verheijden et al 2010, Kassmann 2014.…”
Section: Introductionmentioning
confidence: 99%
“…By transfecting neuronal cell models of HD with a unique pexophagy marker, and imaging the cells longitudinally, we showed that pexophagy is increased in primary neuronal models of HD. Next, we tested the hypothesis that markers of peroxisomes, as well as pexophagy, will be affected by the overexpression of mutant huntingtin, using immunohistochemistry analysis of cortical sections of the mouse brain in young wild-type mice and a BACHD mouse model of Huntington disease (Gray, Shirasaki et al 2008), staining for PEX5, a peroxisomal protein involved in pexophagy, and ACAA1, a peroxisomal marker (Berger, Dorninger et al 2015, Morvay, Baes et al 2017, Eun, Lee et al 2018, Islinger, Voelkl et al 2018. Our results showed that PEX5 and ACAA1 were both reduced in cortical neurons of the BACHD mouse model.…”
Section: Huntington Disease Introductionmentioning
confidence: 99%